Interpretative strategies of lung function tests: obstructive pattern - Tafuro, Federica; Corradi, Massimo; Mutti, Antonio (La Medicina del Lavoro, 2014)
Introduction: Periodic spirometric assessment is critical in the health surveillance of workers who are exposed to respiratory pollutants and plays a key role in the prevention of occupational lung diseases. Objectives: The aim of this review is to provide updates on the proper spirometry examination procedure and the criteria for data interpretation, in order to correctly diagnose obstructive impairment and longitudinal decline of pulmonary function. Methods: A review of the most recent scientific literature was carried out focusing on those papers dealing with spirometric techniques, choice of reference values, and criteria for data interpretation. Results: Over the years, the use of different diagnostic algorithms and reference values have led to poor clarity among users as well as diagnostic misclassifications. Conclusions: For spirometric data reliability it is mandatory to perform appropriate pulmonary function tests, make a correct selection of reference values and use updated interpretive criteria.